Komunikasi Interpersonal Antara Pemain Game Mobile Legends Pada Komunitas Sibakukek Lubuk Pakam - Kusuma, Muhammad Dimas Rizky Harni; Fikri, Muhammad Al; Kamal, Aulia (CV. Pusdikra Mitra Jaya, 2024)
This research aims to determine form and communication interpersonal relationship between Mobile Legends game players in the Sibakukek community in Lubuk Pakam. To answer that, this research uses studies field on community behavior in the Sibakukek community in Lubuk Pakam. Data was collacted using interviews, observation and methods documentation to be analyzed descriptively-Qualitatively using theory interpersonal communication. The research result show two things; First Interpersonal communication is the most common form of communication in Sibakukek community.This communication appears in verbal and non-verbal form verbal. Non-verbal forms are more dominatly used in game through features chat in the game because its is considered more flexible. Meanwhile, the verbal form worn only when they are outside the game. Second, communication interpersonal relationsship betwen Mobile Legends game players in the Sibakukek community has two obstacles, namely; (1) behavioral barriers, form attitudes or behavior be it form the communcator or the communication; (2) ecological barriers, in the form of interference form the environment during the communication process.